Student behaviour and emotional challenges for teachers and parents in Hong Kong. (28th June 2013) - Forlin, Chris; Cooper, Paul
<x xml:space="preserve">Abstract</x> Social, emotional, and behavioural disorders of children, within the context of a whole‐school approach to inclusion as adopted by Hong Kong, can be challenging for teachers and parents. Based on a comprehensive review of the literature and feedback from a range of experts and parent groups in Hong Kong, specific scales were developed to measure four behavioural traits identified in local school‐aged children and the impact these have on their teachers and parents. Completed surveys were obtained from 914 members of school staff and 573 parents of school‐aged children. This research, carried out by Chris Forlin and Paul Cooper of the Hong Kong Institute of Education, led to the identification of substantial levels of student behavioural problems in relation to educational engagement, motivation, co‐operativeness and oppositionality. Evidence of emotional burden from these problems was also identified on parents and teachers. Discussion focuses on areas of potential stress in the school situation and possible points of influence in the home.